Pemberdayaan Generasi Muda Dalam Peningkatan Pariwisata Melalui Seni "Genderang Sisibah" Sebagai Upaya Memperkuat Identitas Budaya Masyarakat Pakpak - Tasya Amelia Saragi; Revayani Sagala; Nila Dwi Amalia; Shiwi Sulistyani; Anggi Nur Febriani; Syamsul Arief; Lasenna Siallagan (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Youth as pillars of the nation are expected by society to carry out their status and role optimally, have a nationalist spirit, and have self-resilience in the influence of globalization. Youth can channel their potential by participating in improving the regional tourism sector through the art of "Genderang Sisibah" which is a collection of perfect musical instruments. In research using qualitative research with literature review or literature study methods, the aim of this research is to find deeper meanings to the art object "Genderang Sisibah", the idea of ??applying tradition to the tourism sector by empowering the younger generation of Pakpak and strengthening efforts cultural identity, with research steps, finding information, understanding, finding meaning, drawing conclusions with development ideas that will be given. The results of the research are appropriate tourism strategies and are the key to success in promoting Sisibah Drum art so that it attracts tourist interest. Keywords: Culture, Pakpak, Young Generation, Sisibah Drum, Tourism.